A peek into academic (de)motivation of undergraduates at India's top engineering schools. (3rd July 2020) - Prasad, Mousami; Sengupta, Sourav; Niranjan, Tarikere T.
ABSTRACT: This study provides an insider's perspective on why engineering undergraduates at elite Indian universities lack academic motivation. Using interpretive qualitative research (actors approach), we uncover students' perceptions of academic (de)motivation and group them into three broad categories: faculty-related, course-related and cognitive-related, which we then explain through select motivation theories. The study arrives at two alternate explanations for the (lack of) academic motivation (demotivation and amotivation). The findings help guide decision-making by faculty members, academic administrators and planners.